A Matemática na formação do sargento especialista da força aérea brasileira - Silva, Thais Milena Godoi [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Brazilian Air Force (FAB), whose first name was National Air Forces, was originated with the creation of the Ministry of Aeronautics in 1941. Due to the demand for technicians in order to maintain the various military organizations within FAB, the School of Aeronautical Specialists (EEAR) was created in the same year. EEAR is the military organization responsible for the training and capacitation of Non-commissioned officers in Aviation and it is currently based in the city of Guaratinguetá. For the training of Non-commissioned officers within FAB, the Training Course for Sergeants (CFS), offered by EEAR, comprised of two years, covers the specialized military and technical areas, as well as instruction in the general field, for the leveling of students' knowledge. Basic Mathematics is one of the subjects that need to be taken in order to complete the course. The topics studied in this subject assists in the training of students in relation to their respective specialties. Therefore, this work aims to analyze the topics studied by the students in the Basic Mathematics subject that is part of the CFS course. Thus, a qualitative research was developed, in which the data was collected through a study of relevant documentation and the use of a questionnaire to those responsible for each specialty. The analysis indicates the need for a reformulation in the syllabus of Basic Mathematics, given to each specialty in EEAR

Com a criação do Ministério da Aeronáutica, em 1941, foi criada a Força Aérea Brasileira (FAB), cujo primeiro nome foi Forças Aéreas Nacionais. Diante da necessidade de técnicos para manter as diversas organizações militares da FAB, no mesmo ano foi criada a Escola de Especialistas de Aeronáutica (EEAR). A EEAR é a organização militar responsável pela formação e aperfeiçoamento dos Graduados da Aeronáutica e atualmente está localizada na cidade de Guaratinguetá. Para a formação dos Graduados da FAB, o Curso de Formação de Sargentos (CFS), oferecido pela EEAR, com duração de dois anos, abrange além da área militar e técnica especializada, a instrução no campo geral, para o nivelamento do conhecimento dos alunos. Dentre as disciplinas a serem cursadas para a conclusão do curso está a disciplina de Matemática Básica. O conteúdo estudado nessa disciplina auxilia na formação dos alunos quanto as suas respectivas especialidades. Diante disso, este trabalho em por objetivo analisar o conteúdo estudado pelos alunos na disciplina de Matemática Básica presente no CFS. Para tanto, foi realizado uma pesquisa qualitativa onde os dados oram coletados através de estudo documental e da aplicação de um questionário aos responsáveis pelos galpões de cada especialidade. A análise realizada indica a necessidade de realização de uma reformulação na ementa de Matemática Básica aplicada a cada especialidade na EEAR
The Mathematics in the formation of the sergeant specialist of the Brazilian air force
Keywords: Matemática - Estudo e ensino; Aeronáutica; Formação profissional; Mathematics Study and teaching